Penyuluhan Pemanfaatan Minyak Atsiri Cengkeh dan Serai sebagai Aromaterapi Aplikasi Parfum Masker - Lusia Eka Putri; Rustini Rustini; Sefrianita Kamal; Sara Surya; Rosiana Rizal; Nofrizal Nofrizal; Nurunnisa Aprilya Yulfi; Widia Rahma Putri; Laras Alhabil (LPPM Universitas Dharma Andalas, 2022)
Indonesia is one of the countries that has the potential as a producer of essential oils. Plant parts that can be used as a source of essential oils are the roots, stems, leaves, flowers, and so on. In the midst of the current pandemic, where the number of COVID-19 cases is increasing day by day. This requires us to maintain our immune system and always comply with health protocols, one of which is the use of masks. The use of the mask for more than 4-5 hours will cause an unpleasant odor. The outreach activity on the use of essential oils of citronella and cloves as aromatherapy in the application of perfume masks is an alternative that can be used by the public to overcome the negative impacts of using masks that last more than 4-5 hours. With this outreach activity, it is hoped that the community can apply, implement and stay healthy in the midst of the epidemic that hit. In maintaining endurance, we must relax ourselves so that we can foster creativity and remain productive in carrying out daily activities.